Culture and consumption theory and decoloniality: an integrative review of recent research - Ferreira, Jonathan; Silva, Adriana Comini da; Santos, Anne Carolina dos; Sperandio, Melissa Rizzo; Pepece, Olga Maria Coutinho (Brazilian Journal of Production Engineering, 2025)
This article aims to conduct a bibliometric study to map and understand the field of studies that relates the Theory of Culture and Consumption and Decoloniality. Considering that consumption is a social phenomenon permeated by symbolic and cultural issues, its analysis from a decolonial perspective becomes fundamental, especially due to the historical European hegemony over subjectivity, culture and knowledge production. The research was conducted in four databases, covering national and international journals, with a time frame from 2017 to 2022. After the search and analysis process, 21 articles were selected. The evaluation focused on the methodologies, objects of study and general objectives of the articles analyzed. For the statistical analysis, the Iramuteq software was used, which allowed the construction of a Descending Hierarchical Classification (DHC), making it possible to identify the frequency and lemmatization of the linguistic forms present in the texts. The results indicate that the majority of articles published in this area are linked to Latin American academic institutions. Furthermore, it is observed that studies, from a decolonial perspective, seek to explain transformations in consumption practices or resignify them as spaces of confrontation between the ideologies of the colonizer and the colonized.